Are We Ill Because We Age? - Fulop, Tamas; Larbi, Anis; Khalil, Abdelouahed; Cohen, Alan A.; Witkowski, Jacek M. (Frontiers in Physiology, 2019)
Growing elderly populations, sometimes referred to as gray (or silver) tsunami, are an increasingly serious health and socioeconomic concern for modern societies. Science has made tremendous progress in the understanding of aging itself, which has helped medicine to extend life expectancies. With the increase of the life expectancy, the incidence of chronic age-related diseases (ARDs) has also increased. A new approach trying to solve this problem is the concept of geroscience. This concept implies that the aging process itself is the common cause of all ARDs. The corollary and consequence of such thinking is that we can and should treat aging itself as a disease. How to translate this into the medical practice is a big challenge, but if we consider aging as a disease the problem is solved. However, as there is no common definition of what aging is, what its causes are, why it occurs, and what should be the target(s) for interventions, it is impossible to conclude that aging is a disease. On the contrary, aging should be strongly considered not to be a disease and as such should not be treated; nonetheless, aging is likely amenable to optimization of changes/adaptations at an individual level to achieve a better functional healthspan.